Una mirada al proceso de restitución de tierras desde la accountability social (2022)
The objective of this research is to carry out an analysis of the management and compliance of the land repair process through Social Accountability carried out by the Land Restitution Unit, an entity that was created with Law 1448 of 2011, in charge of the reestablishment of rights and full reparation to all those people who, as of January 1, 1991, were forced to leave their lands as a consequence of the armed conflict that Colombia has experienced for so many years. The type of research that was carried out was of a documentary and exploratory nature, since we went to different sources of information for the development of this study, where the data published in the reports of the aforementioned entity in charge were taken, in such a way that they could determine the degree of progress in this process in its different stages from the entry into force of the Law until December 31, 2021. On the other hand, it is important to highlight the importance of Social Accountability, which consists of the responsibility that we citizens have in carrying out social control of state entities, in such a way that as professionals in accounting sciences, we can support the review of the management of these entities